乡村振兴中韧性发展的经济-社会政策与共同富裕效应 (The economic-social policy of resilient development and common prosperity in the construction of new development paradigm and Rural Revitalisation) - 思斌, 王 (China journal of social work, 2022)
乡村振兴是新发展格局建构的重要组成部分, 乡村在多大程度上得以振兴, 乡村振兴对构建国内大循环的新发展格局能够产生多大影响, 要看能在多大程度上缩小已形成的城乡过大差距, 改变农村的弱势化、边缘化状态, 以及提升农村农民参与乡村振兴的意愿和能力。由于简单的、一般化的"经济-社会政策支持"难以解决那些已经和仍在边缘化的中西部农村的振兴问题, 要实现其振兴, 必须有韧性地介入, 包括实施有韧性的政策和发展农村的坚韧力。在此背景下, 中西部乡村的振兴发展需要韧性发展的经济-社会政策。因为它是以乡村振兴为本的政策, 是能促进乡村韧性发展的经济-社会政策, 目的是促进乡村经济发展、提振乡村人气和经济社会生活。它同时还是政策群, 包括县域经济的振兴发展, 实施有利于社会发展的经济政策, 实施好公共政策和社会政策, 并使它们整合发展, 进而促进乡村的共同富裕。(Rural Revitalisation is an important part of the construction of the new development paradigm. In this context, the revitalisation and development of rural areas in the central and western regions need economic-social policies for resilience development. It is an economic and social policy focusing on Rural Revitalisation, which can promote rural resilient development with the purpose of promoting rural economic development, boosting rural popularity and raising the level of economic and social life in rural areas. It is a policy group, including the revitalisation and development of county economy, the implementation of economic policies conducive to social development, the implementation of public policies and social policies, and the mechanism of enabling them integrative development. All the above eventually contributes to the development of common prosperity of the rural.)